Fracture resistance of glazed, full-contour ZLS incisor crowns - Schwindling, Franz Sebastian; Rues, Stefan; Schmitter, Marc (Journal of prosthodontic research, 2017)
Purpose: To compare the failure behaviour of zirconia-reinforced lithium silicate (Celtra Duo, DeguDent) with that of lithium disilicate (IPS e.max CAD, Ivoclar Vivadent) and feldspar (Mark II, VITA) ceramics. Methods: Three groups of sixteen glazed maxillary incisor crowns were produced. The inner surfaces of the crowns were etched, then luted to metal dies with self-adhesive cement. Single load-to-failure tests were performed before and after thermo-mechanical ageing. To simulate clinical conditions, the specimens were thermocycled (10,000 cycles between 6.5°C and 60°C) and underwent chewing simulation (1,200,000 cycles, Fmax=86N). Statistical analyses were performed by use of non-parametric Kruskal-Wallis and Mann-Whitney U-tests. Results: Before ageing, all the monolithic incisor crowns fractured at test forces >285N. Mean fracture loads were highest for zirconia-reinforced lithium silicate (725N, SD 162N), slightly lower for lithium disilicate (701N, SD 276N), and lowest for feldspar (554N, SD 190N). The differences between the results were not statistically significant. After ageing, fracture resistance decreased for all materials except zirconia-reinforced lithium silicate. Mean fracture loads were highest for zirconia-reinforced lithium silicate (766N, SD 98N) and significantly lower for both lithium disilicate (485N, SD 64N) and feldspar (372N, SD 116N). Conclusion: Monolithic restorations fabricated from zirconia-reinforced lithium silicate retain high fracture resistance after extensive thermo-mechanical ageing. This preclinical study suggests that cohesive failures of monolithic anterior crowns produced of these ceramics will not be a major problem in dental practice.